Sistem Informasi Berbasis Web Pada Pesantren Mahasiswa ITS PKU Muhammadiyah Surakarta - Hery Siswanto; Muhammad Waskito Aji; Siti Shofiyatun; Nurul Kholisatul ‘Ulya (Universitas Katolik Widya Karya Malang, 2023)
The development of information technology always experiences significant growth in line with human needs, especially in the computer field. The use of information technology is starting to spread to several aspects of the field, one of which is education. The ITS PKU Muhammadiyah Surakarta student Islamic boarding school is an educational institution that is also a place to live to improve religious knowledge and soft skills. In terms of information notification, the Pesma information process, such as activities regarding Pesma, Pesma registration, distribution of Pesma waves, Pesma payment information, and Pesma graduation is carried out via WhatsApp media. Apart from that, student data management still uses Excel which is separate from one data to another. Based on some of the problems above, this will become an obstacle to the Pesma activity process so that it runs less well and effectively. In this research, a web-based information system will be designed which can be a solution to facilitate the delivery of information to students and data management for Pesma officers. The method used for system development is the prototyping method. Prototyping is a software development method that allows users to have an initial idea of the program to be developed and carry out initial testing. From the results of this research, the information system design that has been created is in accordance with the functional needs of business processes in the ITS PKU Muhammadiyah Student Islamic Boarding School environment.